Micro Planning for Biodiversity Conservation and Livelihood Security in Large Landscapes - Key Challenges - Mishra, B.K.; Badola, Ruchi; Bhardwaj, A.K. (Indian Forester, 2014)
Village micro planning for achieving the dual objectives of wildlife conservation and livelihood security is a multi stakeholder led complex and dynamic process that empowers the community analysing their own situation and work on it to create a better future. Aggregated at the landscape level, the micro plans represent the sum total of all such activities that would enhance conservation status of the entire landscape and ensure developmental aspirations of all stakeholders which is the essence of landscape management. However, in recent past, micro plans prepared and implemented around many protected areas of India have faced severe criticisms that they were ineffective in their attempts to serve the communities as well as protected areas. Neither there is any systematic documentation of the micro planning process, nor a how-to-do-it guideline for preparing village micro plans. This paper therefore is an attempt to address this gap besides drawing together a number of issues about which the planning team needs to be sensitized so that they can handle various challenges that may arise during micro planning work.